A thermal precipitation crystallization process of ammonium hexavanadate
By using ammonium salt liquid feeding and adjusting the reaction temperature in the thermal crystallization process of ammonium hexapolis vanadate, the problems of low bulk density and uneven particle size in traditional processes are solved, and the preparation of high-density, large-particle size ammonium hexapolis vanadate is achieved, which significantly improves the stability and quality uniformity of the product.
Patent Information
- Application Number
- CN202310470754.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-27
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2043-04-27
AI Technical Summary
In traditional processes, the explosive crystallization and incomplete growth of ammonium hexapovanadate lead to low bulk density, uneven particle size distribution, fine particle size, and unstable.
The thermal crystallization process of ammonium hexammonium vanadate is adopted, and the supersaturation of ammonium hexammonium hexammonium vanadate is controlled to stabilize in the mesolidary zone through ammonium salt liquid feeding and reaction temperature adjustment, so as to achieve a crystal growth rate greater than the crystal nucleus generation rate, and obtain high-density, large-particle size ammonium hexammonium hexammonium hexammonium vanadate.
The high-density and large particle size preparation of ammonium hexapovanadate was achieved, with the bulk density increased to 0.6~0.9g/cm3, and the average particle size expanded to 90±3μm~110±6μm, significantly improving the stability and mass uniformity of the product.
Smart Images

Figure SMS_1 
Figure SMS_5
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of hydrometallurgy, and in particular to a thermal precipitation crystallization process of ammonium hexavanadate. Background Art
[0002] Ammonium hexavanadate, (NH4)2V6O 16 It is an intermediate product of the vanadium industry. The quality of its products directly affects the quality of vanadium oxide and vanadium alloy products, especially high-density and large-particle ammonium hexavanadate, which is of great significance to the smelting of vanadium alloys, product quality control, and reducing dust losses.
[0003] In the traditional process, the ammonium hexavanadate produced by acid leaching vanadium solution as raw material and solid ammonium sulfate as precipitant is produced by acidic ammonium salt precipitation process. The explosive crystallization, incomplete crystal nucleus growth, low bulk density, uneven particle size distribution and fine particle size are the main causes of the production. The average bulk density is 0.6g / cm 3 , and is very unstable, with a standard deviation of 0.11 g / cm 3 , the proportion below the average is as high as 51.57%, and the average particle size is less than 60μm.
[0004] After a large amount of data analysis, it was found that the explosive crystallization and incomplete nucleus growth of ammonium hexavanadate in the traditional process led to its low bulk density and uneven particle size distribution. In terms of reaction principle, the precipitant used in the traditional process is solid ammonium salt, which must first be dissolved in the preheated vanadium solution. Its dissolution is not very complete, the reaction is mainly controlled by diffusion, and the crystallization environment is very complex, with high temperature and low acidity. Summary of the invention
[0005] In view of this, the present invention provides a new thermal precipitation crystallization process of ammonium hexavanadate to solve the problems of explosive crystallization, incomplete nucleus growth, low bulk density, uneven particle size distribution, and fine particle size of ammonium hexavanadate produced by traditional processes. The supersaturation of ammonium hexavanadate is more easily controlled to be stable in a metastable zone by adding ammonium salt liquid and adjusting the reaction temperature, thereby achieving a crystal growth rate greater than a nucleus generation rate, and obtaining high-density and large-particle-size ammonium hexavanadate.
[0006] The technical solution adopted by the present invention is as follows:
[0007] The present invention provides a thermal precipitation crystallization process of ammonium hexavanadate, which is characterized by comprising the following steps:
[0008] S1. Acid adjustment at room temperature: add acid to the acidic vanadium solution with a pH of 2.5 to 4.0 to adjust the pH of the solution to 1.5 to 2.0;
[0009] S2, nucleation reaction: heat the acidified solution of S1 to 85-92°C, add ammonium salt solution at a uniform rate for 5-10 minutes, and continue to add acid to maintain the pH of the solution at 1.5-2.0. + The mass ratio of vanadium to the solution is 0.057:1 to 0.136:1;
[0010] S3, crystal growth and polymerization: the solution treated in S2 is heated to 92-95°C, and the ammonium salt solution of the same concentration is added at the same rate as in S2, and the total NH4 added in steps S2 and S3 is controlled. + The mass ratio of the vanadium in the solution is 0.27:1 to 0.38:1, and concentrated sulfuric acid is continuously added to maintain the pH of the solution at 1.5 to 2.0, and the reaction is carried out for 50 to 80 minutes;
[0011] S4, heat preservation and washing: after the reaction is completed, the vanadium precipitation product is heat-insulated and washed with hot water at 92-95°C, and then ground and sieved after drying to obtain ammonium hexavanadate crystals.
[0012] In one embodiment of the present invention, S2 and S3 maintain the NH4 added per minute. + The mass ratio of vanadium to vanadium in the solution is 0.011:1 to 0.014:1.
[0013] In one embodiment of the present invention, the vanadium concentration of the acidic vanadium solution in S1 is 20-30 g / L.
[0014] In one embodiment of the present invention, the acid solution described in S1 and S2 is concentrated sulfuric acid or dilute sulfuric acid; preferably, the acid solution described in S1 and S2 is concentrated sulfuric acid.
[0015] In one embodiment of the present invention, the ammonium salt described in S2 is ammonium sulfate.
[0016] In one embodiment of the present invention, stirring is performed when the ammonium salt is added to S2.
[0017] In one embodiment of the present invention, the bulk density of the ammonium hexavanadate crystals obtained in S4 is 0.6 to 0.9 g / cm 3 The average particle size is 90±3μm~110±6μm.
[0018] Due to the adoption of the above technical solution, the beneficial effects of the present invention are as follows:
[0019] The invention provides a thermal precipitation crystallization process of ammonium hexavanadate, i.e., a process of acid adjustment at room temperature → rapid nucleation at low temperature → slow growth and polymerization at medium temperature → separation by insulation at medium temperature. Compared with a traditional ammonium solid-state addition method, the difference lies in that an ammonium salt precipitant is prepared into a solution of a certain concentration, a vanadium-containing raw material is continuously added at a certain rate, the reaction time and reaction temperature of each stage are controlled, and the supersaturation of the ammonium hexavanadate is more easily controlled to be stable in a metastable zone, thereby ensuring that the crystal growth rate is greater than the crystal nucleation rate, and finally obtaining high-density and large-particle-size ammonium hexavanadate. DETAILED DESCRIPTION
[0020] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0021] According to the bulk density, porosity and ellipsoid volume formula, NH4V3O8 and (NH4)2V6O 16 Molar mass, derived bulk density ρ B The relationship between the phase purity x of ammonium hexavanadate, the porosity ε, and the ellipsoid geometric size abc is as follows:
[0022]
[0023] Where: B —Bulk density, g / cm 3 ; m—mass, g; V B —Pile volume, cm 3 ; ε—porosity; ρ P —Accurate density, g / cm 3 ; V P —Solid volume, cm 3 ; abc—ellipsoid axis radius, μm; n—molar mass or degree of polymerization, mol; x—phase (NH4)2V6O 16 Purity; N-phase (NH4)2V6O 16 The number of grains.
[0024] The above expression shows that the sufficient condition for the density of ammonium hexavanadate to increase is the phase (NH4)2V6O 16 As the purity increases, the degree of polymerization or molar mass of the phase increases; the porosity decreases, the number of crystals decreases, and the particle size increases.
[0025] The present invention provides a thermal precipitation crystallization process of ammonium hexavanadate, the steps of which are as follows:
[0026] S1. Acid adjustment at room temperature: Acid solution is added to the acidic vanadium solution with a pH of 2.5-4.0 to adjust the pH of the solution to 1.5-2.0. During this process, the reactions occurring in the solution are as follows:
[0027]
[0028] S2, nucleation reaction: heat the acidified solution of S1 to 85-92°C, add ammonium salt solution at a uniform rate for 5-10 minutes, and continue to add acid to maintain the pH of the solution at 1.5-2.0. + The mass ratio of vanadium to the solution is 0.057:1 to 0.136:1. The reaction in this step is as follows:
[0029]
[0030] S3, crystal growth and polymerization: the solution treated in S2 is heated to 92-95°C, and the ammonium salt solution of the same concentration is added at the same rate as in S2, and the total NH4 added in steps S2 and S3 is controlled. + The mass ratio of vanadium to the solution is 0.27:1 to 0.38:1, and concentrated sulfuric acid is continuously added to maintain the pH of the solution at 1.5 to 2.0, and the reaction is carried out for 50 to 80 minutes. In the process of adding the ammonium salt solution, there are both nucleation reaction, crystal growth reaction, and crystal polymerization reaction, but the crystal growth rate is greater than the nucleation rate. The reaction formula of the nucleation reaction is the same as the reaction formula of step S2, and the reaction formula of the crystal growth is as follows:
[0031]
[0032] The reaction equation of crystal polymerization is as follows:
[0033]
[0034] S4, heat preservation and washing: after the reaction is completed, the vanadium precipitation product is heat-insulated and washed with hot water at 92-95°C, and then ground and sieved after drying to obtain ammonium hexavanadate crystals.
[0035] The technical solution of the present invention is specifically described below through examples.
[0036] Example 1
[0037] This embodiment provides a thermal precipitation crystallization process of ammonium hexavanadate
[0038] S1. Acid adjustment at room temperature: Take 300 mL of an acidic vanadium solution with a vanadium concentration of 29.75 g / L and a pH of 2.65, and add concentrated sulfuric acid at room temperature to adjust the solution pH to 1.8;
[0039] S2, nucleation reaction: The acid-adjusted solution of S1 was placed in a water bath at 85°C, and a 300 g / L ammonium sulfate solution was added at a rate of 1.19 mL / min by a peristaltic pump under a certain stirring intensity for 7 min, while concentrated sulfuric acid was continuously added to maintain the solution pH at 1.8;
[0040] S3, crystal growth and polymerization: the solution treated with S2 was heated to 95°C, and a 300 g / L ammonium sulfate solution was added at a rate of 1.19 mL / min by a peristaltic pump under a certain stirring intensity to control the total amount of NH4 added in steps S2 and S3. + The mass ratio of vanadium to the solution was 0.327:1, and concentrated sulfuric acid was continuously added to maintain the solution pH at 1.8, and the reaction lasted for 53 minutes;
[0041] S4, heat preservation and washing: after the reaction in S3 is completed, the vanadium precipitation product is washed with hot water at 95°C, and then ground and sieved after drying to obtain ammonium hexavanadate crystals.
[0042] The bulk density of the ammonium hexavanadate crystals obtained in this example is 0.88 g / cm 3 , the average particle size is 103.55±4.21μm.
[0043] The ammonium hexavanadate crystals prepared in this embodiment meet the requirements of high-density and large-size ammonium hexavanadate.
[0044] Example 2
[0045] This embodiment provides a thermal precipitation crystallization process of ammonium hexavanadate
[0046] S1. Acid adjustment at room temperature: Take 300 mL of an acidic vanadium solution with a vanadium concentration of 20 g / L and a pH of 2.65, and add concentrated sulfuric acid at room temperature to adjust the solution pH to 1.5;
[0047] S2, nucleation reaction: The acid-adjusted solution of S1 was placed in a water bath at 85°C, and a 250 g / L ammonium sulfate solution was added at 1.0 mL / min by a peristaltic pump under a certain stirring intensity for 5 min, while concentrated sulfuric acid was continuously added to maintain the solution pH at 1.5;
[0048] S3, crystal growth and polymerization: the solution treated with S2 was heated to 95°C, and a 250 g / L ammonium sulfate solution was added at a rate of 1.0 mL / min by a peristaltic pump under a certain stirring intensity to control the total amount of NH4 added in steps S2 and S3. + The mass ratio of vanadium to the solution was 0.273:1, and concentrated sulfuric acid was continuously added to maintain the solution pH at 1.5, and the reaction lasted for 80 minutes;
[0049] S4, heat preservation and washing: after the reaction in S3 is completed, the vanadium precipitation product is washed with hot water at 95°C, and then ground and sieved after drying to obtain ammonium hexavanadate crystals.
[0050] The bulk density of the ammonium hexavanadate crystals obtained in this example is 0.80 g / cm 3 , the average particle size is 100.31±5.51μm.
[0051] The ammonium hexavanadate crystals prepared in this embodiment meet the requirements of high-density and large-size ammonium hexavanadate.
[0052] Example 3
[0053] This embodiment provides a thermal precipitation crystallization process of ammonium hexavanadate
[0054] S1. Acid adjustment at room temperature: Take 300 mL of an acidic vanadium solution with a vanadium concentration of 30 g / L and a pH of 2.65, and add concentrated sulfuric acid at room temperature to adjust the solution pH to 2.0;
[0055] S2, nucleation reaction: The acid-adjusted solution of S1 was placed in a water bath at 85°C, and a 350 g / L ammonium sulfate solution was added at a rate of 1.28 mL / min by a peristaltic pump under a certain stirring intensity for 10 min, while concentrated sulfuric acid was continuously added to maintain the solution pH at 2.0;
[0056] S3, crystal growth and polymerization: the solution treated with S2 was heated to 95°C, and a 350 g / L ammonium sulfate solution was added at a rate of 1.28 mL / min by a peristaltic pump under a certain stirring intensity to control the total amount of NH4 added in steps S2 and S3. + The mass ratio of vanadium to the solution was 0.382:1, and concentrated sulfuric acid was continuously added to maintain the solution pH at 2.0, and the reaction was continued for 50 minutes;
[0057] S4, heat preservation and washing: after the reaction in S3 is completed, the vanadium precipitation product is washed with hot water at 95°C, and then ground and sieved after drying to obtain ammonium hexavanadate crystals.
[0058] The bulk density of the ammonium hexavanadate crystals obtained in this example is 0.78 g / cm 3 , the average particle size is 98.87±3.51μm.
[0059] The ammonium hexavanadate crystals prepared in this embodiment meet the requirements of high-density and large-size ammonium hexavanadate.
[0060] Comparative Example 1
[0061] This comparative example provides a thermal precipitation crystallization process of ammonium hexavanadate
[0062] The process is basically the same as that of Example 1, except that the concentration of the ammonium sulfate solution in steps S2 and S3 is 200 g / L.
[0063] The bulk density of the ammonium hexavanadate crystals obtained in this comparative example is 0.46 g / cm 3 , the average particle size is 108.31±4.31μm.
[0064] The bulk density of the ammonium hexavanadate crystals prepared in this comparative example does not meet the requirements of high-density and large-particle-size ammonium hexavanadate.
[0065] Comparative Example 2
[0066] This comparative example provides a thermal precipitation crystallization process of ammonium hexavanadate
[0067] The process is basically the same as that of Example 1, except that the concentration of the ammonium sulfate solution in steps S2 and S3 is 400 g / L.
[0068] The bulk density of the ammonium hexavanadate crystals obtained in this comparative example is 0.48 g / cm 3 , the average particle size is 86.51±4.34μm.
[0069] The bulk density and particle size of the ammonium hexavanadate crystals prepared in this comparative example do not meet the requirements of high-density and large-particle-size ammonium hexavanadate.
[0070] Comparative Example 3
[0071] The process is basically the same as that of Example 1, except that the rate of dropping the ammonium sulfate solution in steps S2 and S3 is instantaneous addition.
[0072] The bulk density of the ammonium hexavanadate crystals obtained in this comparative example is 0.69 g / cm 3 , the average particle size is 52.67±6.56μm.
[0073] The particle size of the ammonium hexavanadate crystals prepared in this comparative example does not meet the requirements of high-density and large-particle-size ammonium hexavanadate.
[0074] Comparative Example 4
[0075] The process is basically the same as that of Example 1, except that in steps S2 and S3, an ammonium sulfate solution with a concentration of 300 g / L is added at 0.60 mL / min.
[0076] The bulk density of the ammonium hexavanadate crystals obtained in this comparative example is 0.79 g / cm 3 , the average particle size is 71.20±4.81μm.
[0077] The particle size of the ammonium hexavanadate crystals prepared in this comparative example does not meet the requirements of high-density and large-particle-size ammonium hexavanadate.
[0078] Comparative Example 5
[0079] The process is basically the same as that of Example 1, except that the reaction temperature is maintained at 85° C. in step S3.
[0080] The bulk density of the ammonium hexavanadate crystals obtained in this comparative example is 0.34 g / cm 3 , the average particle size is 141.56±105.53μm.
[0081] The particle size fluctuation of the ammonium hexavanadate crystals prepared in this comparative example is too large. Therefore, the bulk density and particle size of the ammonium hexavanadate crystals prepared in this comparative example do not meet the requirements of high-density and large-particle-size ammonium hexavanadate.
[0082] Comparative Example 6
[0083] The process is basically the same as that of Example 1, except that the reaction temperature is maintained at 98° C. in step S3.
[0084] The bulk density of the ammonium hexavanadate crystals obtained in this comparative example is 0.31 g / cm 3 , the average particle size is 80.45±5.20μm.
[0085] The bulk density and particle size of the ammonium hexavanadate crystals prepared in this comparative example do not meet the requirements of high-density and large-particle-size ammonium hexavanadate.
[0086] Comparative Example 7
[0087] The process is basically the same as that in Example 1, except that the total amount of NH4 added in step S3 is controlled to be + The mass ratio of / V is 0.22:1.
[0088] The bulk density of the ammonium hexavanadate crystals obtained in this comparative example is 0.30 g / cm 3 , the average particle size is 70.01±5.44μm.
[0089] The bulk density and particle size of the ammonium hexavanadate crystals prepared in this comparative example do not meet the requirements of high-density and large-particle-size ammonium hexavanadate.
[0090] Comparative Example 8
[0091] The process is basically the same as that in Example 1, except that the total amount of NH4 added in step S3 is controlled to be + The mass ratio of / V is 0.44:1.
[0092] The bulk density of the ammonium hexavanadate crystals obtained in this comparative example is 0.37 g / cm 3 , the average particle size is 87.79±4.61μm.
[0093] The bulk density and particle size of the ammonium hexavanadate crystals prepared in this comparative example do not meet the requirements of high-density and large-particle-size ammonium hexavanadate.
[0094] In summary, in the thermal crystallization process of ammonium hexavanadate, the concentration and rate of ammonium salt solution addition, the reaction time at different stages, the crystallization temperature, the total NH4 + The mass ratio of / V and other aspects have a significant impact on the bulk density and particle size of the hexapolyammonium vanadate crystals. The process of the present invention is used to control the concentration of the salt solution added and the rate of adding the ammonium salt solution, the reaction time at different stages, the crystallization temperature, the total NH4 + When the mass ratio of / V is within an appropriate range, high-density and large-size ammonium hexavanadate can be obtained.
[0095] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A thermal crystallization process of ammonium hexavanadate, characterized in that: The steps include: S1. Acid adjustment at room temperature: add acid to the acidic vanadium solution with a pH of 2.5 to 4.0 to adjust the pH of the solution to 1.5 to 2.0; S2, nucleation reaction: heat the acidified solution of S1 to 85-92°C, add ammonium salt solution at a constant rate for 5-10 minutes, and continue to add acid to maintain the pH of the solution at 1.5-2.
0. + The mass ratio of vanadium to the solution is 0.057:1 to 0.136:1; S3, crystal growth and polymerization: the solution treated with S2 is heated to 92-95°C, and the ammonium salt solution of the same concentration is added at the same rate as in S2, and the total NH4 added in steps S2 and S3 is controlled. + The mass ratio of vanadium to the solution is 0.27:1 to 0.38:1, and concentrated sulfuric acid is continuously added to maintain the pH of the solution at 1.5 to 2.0, and the reaction is carried out for 50 min to 80 min; S4, heat preservation and washing: after the reaction is completed, the vanadium precipitation product is washed with hot water at 92-95°C, and then ground and sieved after drying to obtain ammonium hexavanadate crystals; S2 and S3 maintain the addition of NH4 per minute + The mass ratio of the vanadium in the solution is 0.011:1 to 0.014:1; The vanadium concentration of the acidic vanadium solution described in S1 is 20 to 30 g / L.
2. A method for thermal crystallization of ammonium hexavanadate according to claim 1, characterized in that: The acid solution described in S1 and S2 is one of concentrated sulfuric acid or dilute sulfuric acid.
3. A thermal crystallization process of ammonium hexavanadate according to claim 1, characterized in that: The ammonium salt described in S2 is ammonium sulfate.
4. A thermal crystallization process of ammonium hexavanadate according to claim 1, characterized in that: When the ammonium salt is added to S2, stirring is also performed.
5. A thermal crystallization process of ammonium hexavanadate according to claim 1, characterized in that: The bulk density of the ammonium hexavanadate crystals obtained in S4 is 0.6-0.9 g / cm 3 The average particle size is 90±3 μm~110±6 μm.